How to save van Fraassen’s own antirealism: a modest proposal - Alessio Gava (Perspectiva Filosófica)
Bas van Fraassen’s antirealist view of science and its aim, constructive empiricism, notoriously rests upon a distinction between observable and unobservable entities. In order to back his empiricist stance, the Dutch philosopher put forward his own characterization of observability. Nonetheless, he acknowledges that the point of constructive empiricism is not lost if the line is drawn in a somewhat different way from how he draws it. This means that other characterizations of observability can support this antirealist stance, provided they allow for a viable distinction between the observable and the unobservable. The aim of this work, however, is not to propose another characterization of observability that fits constructive empiricism, but to put forward a little amendment to van Fraassen’s own antirealism, to the effect that it can actually be seen as a coherent position, albeit controversial, since its present consistency might be called into question.